Development of a core outcome set for amblyopia, strabismus and ocular motility disorders: a review to identify outcome measures - Samia Al Jabri (BMC Ophthalmology, 2019)
Abstract Background Core Outcome Sets (COS) are defined as the minimum sets of outcomes that should be measured and reported in all randomised controlled trials to facilitate combination and comparability of research. The aim of this review is to produce an item bank of previously reported outcome measures from published studies in amblyopia, strabismus and ocular motility disorders to initiate the development of COS. Methods A review was conducted to identify articles reporting outcome measures for amblyopia, strabismus and ocular motility disorders. Using systematic methods according to the COMET handbook we searched key electronic bibliographic databases from 1st January 2011 to 27th September 2016 using MESH terms and alternatives indicating the different subtypes of amblyopia, strabismus and ocular motility disorders in relation to treatment outcomes and all synonyms. We included Cochrane reviews, other systematic reviews, controlled trials, non-systematic reviews and retrospective studies. Data was extracted to tabulate demographics of included studies, primary and secondary outcomes, methods of measurement and their time points. Results A total of 142 studies were included; 42 in amblyopia, 33 in strabismus, and 68 in ocular motility disorders (one study overlap between amblyopia and strabismus). We identified ten main outcome measure domains for amblyopia, 14 for strabismus, and ten common “visual or motility” outcome measure domains for ocular motility disorders. Within the domains, we found variable nomenclature being used and diversity in methods and timings of measurements. Conclusion This review highlights discrepancies in outcome measure reporting within published literature for amblyopia, strabismus and ocular motility and it generated an item bank of the most commonly used and reported outcome measures for each of the three conditions from recent literature to start the process of COS development. Consensus among all stakeholders including patients and professionals is recommended to establish a useful COS.